Commitment to an entrepreneurship training programme for self-employed entrepreneurs, and learning from participation. Issue 7 (8th August 2016) - Nieminen, Lenita; Hytti, Ulla
Abstract : Purpose: The purpose of the article is to explore how self-employed entrepreneurs commit themselves to an entrepreneurship training programme and how such commitment relates to their perceptions of learning. Design/methodology/approach: The data were collected through qualitative, inductive methods by interviewing and observing six entrepreneurs who took part in an entrepreneurship training programme. Findings: The study reveals that entrepreneurial activities and a strong attachment to entrepreneurship may detach entrepreneurs from an entrepreneurship community. Generally, participants appreciated the social aspect of learning, peer support and confidence-building provided by the programme and the learning community. Nevertheless, the participation was a double-edged sword: it allowed those who were not active in entrepreneurship to explore entrepreneurship, but for those who were active in entrepreneurship and in professional communities, their participation represented a potential liability and a threat to their image as a credible entrepreneur. Research limitations/implications: More research is needed on the social aspect related to training programmes particularly focusing on potential adverse outcomes, such as over-embeddedness in the community. Practical implications: Training programme organizers could benefit from understanding the social aspects of learning in emphasizing the role of peer support but also of the potential dark sides of socializing. Originality/value: The study offers insight into the relationship between commitment and learning in micro firms, and it contributes to a deeper understanding of the way community and social relationships facilitate or impede learning by self-employed entrepreneurs. There is a risk that the social aspect of peer support and the community replaces entrepreneurs' need to 'go out there' and expose themselves to learning from experience.